Implementation of Reflective Thinking Skill During COVID-19: EFL Teachers’ Perspectives - Ayu, Ni Kadek Nia Ivana; Myartawan, I Putu Ngurah Wage; Pratiwi, Ni Putu Astiti (STKIP AGAMA HINDU SINGARAJA, 2021)
The aim of this study is to analyze the ability of the English teachers’ reflective thinking skills during online learning at SMAS Laboratorium Undiksha. The design used for this study was a qualitative descriptive study using a questionnaire namely TRTQ (Teacher’s Reflective Thinking Questionnaire) as the instrument that was distributed to three English teachers at SMAS Laboratorium Undiksha as participants in this study. The results of this study showed that all the English teachers in SMAS Laboratorium Undiksha have perceived themselves as advanced teachers in the implementation of reflective thinking practice by doing reflective thinking ability such as (reflective thinking skill, self-assess ability, self-belief, and teaching awareness).